تأثير درجات الحرارة على تغير أعداد حشرة الحمضيات الشمعية Ceroplastes floridensis Comstock على الحمضيات في محافظة اللاذقية (مجلة جامعة اللاذقية- سلسلة العلوم البيولوجية, 2019)
The research was carried out in four citrus orchards of Lattakia, Syria, in the following areas: Kamiliya, Dibba, Sitkheres, and Ain al-Laban. Samples collected weekly from the following Citrus cultivars: Navel orange, Clementine, Java orange from1/6/2017 until 1/3/2018 in addition to taking the degrees of the minimum and maximum temperature weekly from the climatic station in the province of Lattakia  Field readings identified the period of activity of the Citrus wax scale insect, which peaked in adult stage in -Junerate1.6 an adult insect/leaf. Numbers decreased until the end of August rate 1 an adult insect/leaf, and then gradually decreased to December rate 0,1 an adult insect/leaf and disappeared suddenly in January 2018 due to low temperatures, and reappeared in small numbers at the beginning of February 2018, it was found that the insect spends the winter in the adult female insect. A strong correlation found between the number of Citrus wax scale and the average temperature of the week. The highest value of correlation coefficients was on the Clementine r=0,878.     نفذ البحث في أربعة بساتين من محافظة اللاذقية – سورية، في المناطق التالية: الكاملية، دبا، ستخيرس، عين اللبن، جمعت العينات أسبوعياً من الأصناف التالية: أبو صرة، كلمنتين، يافاوي، وأخذت القراءات لكافة أطوار الحشرة الشمعية من 1/6/2017 وحتى 1/3/2018 كذلك أخذت درجات الحرارة الصغرى والعظمى أسبوعياً من المحطة المناخية في محافظه اللاذقية. حددت فترات نشاط حشرة الحمضيات الشمعية من خلال القراءات الحقلية، وبلغت ذروة أعدادها في طور الحشرة البالغة في حزيران بمتوسط 1.6 حشرة بالغة /ورقةوتراجعت الأعداد حتى نهاية آب بمتوسط 1 حشرة بالغة /ورقة، ثم تناقصت أعدادها تدريجياً حتى كانون الأول بمتوسط 0,1 حشرة بالغة/ورقة عام 2017، واختفت فجأة في كانون الثاني عام2018 بسبب انخفاض درجات الحرارة، وعادت للظهور بأعداد قليلة في بداية شباط 2018، وتبين أنها تقضي فصل الشتاء بطور الحشرة البالغة الأنثى. وجد ارتباط طردي قوي بين أعداد بالغات حشرة الحمضيات الشمعية ومتوسطات درجات الحرارة الأسبوعية، وبلغت أكبر قيمة لمعامل الارتباط على صنف كلمنتينr=0,878  .